(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article talks about self-development, personal growth, the place of reading in a person’s life, secrets of skill development, methods of being successful, the role of mutoaladan in the formation of leader’s speech. The role of mutoala in human life is of particular importance. Especially in the maturation of the leader, the role of books in his oratory development is incomparable. Each of us, whichever profession we are, will interact with the book to a certain extent, depending on our capabilities and circumstances. This is how we spend a certain part of our measured life